Reconhecimento de circunstâncias para um projecto de arquitectura. Rua do Heroísmo, 333. - Fábio Veríssimo Santos (2013)
The present dissertation is composed by five distinct moments. The first one, the introduction, advances with the presentation of the investigation and other supportive examples, where is recognized a similar purpose. It also introduces the case study as well as its situation. The second phase presents the different lives that went by the "CCStop". The "Garagem Austin", as a modernist project, in a reflection about the different issues and questions that are related with this building typology. The Commercial Center, the space transformation and consequent atmosphere changes. At last, the alteration for its actual state where, through field work, the principal changes of its uses and shapes are enunciated. There are also pointed the acoustic problems presents in the building caused by its new utilization. The third moment enunciates the methodology and process of the work field, interviews, conversations and observations done close to the social agents. The chapter here presented enunciates clues for possible ways of intervention and gathering of information in similar approaches. At a fourth moment tries to answer the current situation. A shortterm solution, proposals of easy execution that responds to the problems recognized by the musicians. At last, at a second projectual moment, is presented a possibility of program and architecture for the future building, the fourth live of "CCStop", the transition of marginality to acceptance, with the transformation of an urban equipment. Sustaining the this investigation there was recognition of various situations that were used to support our project choices and opinions - surveys of the buildings that were visited, information that was provided and of the people that received us, presented the building and argued with us about our work.